The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.redox.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress and the amyloid beta peptide in Alzheimer’s disease

Abstract: Oxidative stress is known to play an important role in the pathogenesis of a number of diseases. In particular, it is linked to the etiology of Alzheimer’s disease (AD), an age-related neurodegenerative disease and the most common cause of dementia in the elderly. Histopathological hallmarks of AD are intracellular neurofibrillary tangles and extracellular formation of senile plaques composed of the amyloid-beta peptide (Aβ) in aggregated form along with metal-ions such as copper, iron or zinc. Redox active me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
1,313
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,590 publications
(1,363 citation statements)
references
References 209 publications
(285 reference statements)
30
1,313
0
20
Order By: Relevance
“…[2a, 3] In Alzheimer's disease (AD), copper ions bound to extracellular amyloid-β (Aβ) peptide produce ROS and contribute to the oxidative stress observed in the disease. [3] It has indeed been shown that the Cu(Aβ) species can catalyse the incomplete reduction of dioxygen leading to O 2 •- , H 2 O 2 and HO • . [4] In living organisms, efficient pathways to finely tune the concentrations in O 2 ◦- and H 2 O 2 have evolved to protect endogenous components against oxidative damage and to control the ROS concentrations to appropriate levels.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[2a, 3] In Alzheimer's disease (AD), copper ions bound to extracellular amyloid-β (Aβ) peptide produce ROS and contribute to the oxidative stress observed in the disease. [3] It has indeed been shown that the Cu(Aβ) species can catalyse the incomplete reduction of dioxygen leading to O 2 •- , H 2 O 2 and HO • . [4] In living organisms, efficient pathways to finely tune the concentrations in O 2 ◦- and H 2 O 2 have evolved to protect endogenous components against oxidative damage and to control the ROS concentrations to appropriate levels.…”
mentioning
confidence: 99%
“…[15] In the present communication, we used complex 1 + instead of following a classical chelating strategy [16] and using a free ligand that might be toxic. Furthermore in the context of AD, the importance of oxidative stress is widely acknowledged, [3] proving relevant the use of a SOD mimict. We will thus describe here how compound 1 + , which has an interesting intrinsic SOD-like ability, prevents Cu-induced processes by removing Cu(II) from Aβ, that is to say how it prevents ROS production and alteration of Aβ aggregation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance of cell redox state is important to cell viability [43]. The increased level of reactive species can lead to oxidative damage to a vast number of biological molecules, as DNA [44][45][46], proteins [47], lipids [48], including membranes [3] leading to a range of pathologies, as cancer [36], neurological disease [49], cardiac disease [50,51], inflammation process [52] and aging.…”
Section: Cellular Respiration and Generation Of Reactive Species In Tmentioning
confidence: 99%
“…Alzheimer's Disease (AD) is a neurodegenerative disease characterized by aggregation of amyloid peptide and extensive inflammation related to a strong oxidative stress (Cheignon et al, 2018). Metals are known to play a key role in this oxidative stress and also to be associated with peptide aggregation, at the core of the pathology (Faller et al, 2013;Viles, 2012).…”
Section: Chemical Contextmentioning
confidence: 99%